2022
DOI: 10.21093/el-buhuth.v5i01.3734
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Inflasi, Kebebasan Ekonomi Dan Perkembangan Sektor Industri Halal Terhadap Pertumbuhan Ekonomi Negara

Abstract: Umat muslim saat ini memiliki kesadaran yang lebih besar untuk mendapatan produk-produk yang halal baik barang maupun jasa. Optimalisasi perkembangan sektor industri halal bisa meningkat melalui peran keuangan Islam secara langsung untuk menghidupi sektor rill atau dengan membiayai industri halal untuk menciptakan produktivitas dalam pertumbuhan ekonomi. Tujuan penelitian pada penelitian ini adalah untuk mengetahui pengaruh variabel inflasi, kebebasan ekonomi dan perkembangan sektor industri halal terhadap per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Based on the panel data model, no significant influence of economic freedom on economic growth was found. This finding is consistent with previous research by (Elina & Setyadharma, 2022;Quddus, 2022), which also indicated that economic freedom does not have a significant impact on economic growth. These results do not support endogenous economic growth theory, which implies that economic freedom may affect overall macroeconomic conditions but does not directly influence internal factors essential for long-term growth.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the panel data model, no significant influence of economic freedom on economic growth was found. This finding is consistent with previous research by (Elina & Setyadharma, 2022;Quddus, 2022), which also indicated that economic freedom does not have a significant impact on economic growth. These results do not support endogenous economic growth theory, which implies that economic freedom may affect overall macroeconomic conditions but does not directly influence internal factors essential for long-term growth.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the panel data model, no significant influence of economic freedom on economic growth was found. This finding is consistent with previous research by (Elina & Setyadharma, 2022;Quddus, 2022), which also indicated that economic freedom does not have a significant impact on economic growth. These results do not support endogenous economic growth theory, which implies that economic freedom may affect overall macroeconomic conditions but does not directly influence internal factors essential for long-term growth.…”
Section: Discussionsupporting
confidence: 93%
“…In times of rising halal industry, Indonesia's economic growth will rise. This result is undoubtedly under research by Quddus (2022) who research that the Halal Industry positively influences economic growth. Therefore, the government needs to pay serious attention to macro instrument policies to support the increase in national economic growth (Quddus, 2022).…”
Section: Var Estimation Resultsmentioning
confidence: 93%
“…This result is undoubtedly under research by Quddus (2022) who research that the Halal Industry positively influences economic growth. Therefore, the government needs to pay serious attention to macro instrument policies to support the increase in national economic growth (Quddus, 2022). Meanwhile, Islamic Financial Assets do not affect economic growth.…”
Section: Var Estimation Resultsmentioning
confidence: 93%
See 1 more Smart Citation